A comparison of the psychosocial maladjustment of adult males and females sexually molested as children - Hunter, J. A. (Journal of interpersonal violence, 1991)
The long-term sequelae of child sexual abuse were investigated through comparison of matched numbers of nonclinical samples of adult males (n = 24) and females (n = 28) molested as children, and control group subjects on a variety of outcome measures. Results support the association between childhood sexual abuse and adult psychosocial dysfunction for both male and female victims, with victims of both sexes showing more dysfunction than controls on the MMPI, Dyadic Adjustment Scale, Derogatis Sexual Functioning Inventory, and Rosenberg Self-Esteem Scale. Male victims were found to be more likely to have an adolescent perpetrator than females, while females were found to be more likely to have been molested through an incestuous relationship than male victims. Support for the presence of identity conflicts and rumination in males, and body image disturbances in females is discussed